Is There Association Between Changes in eGFR Value and the Risk of Permanent Type of Atrial Fibrillation? - Analysis of Valvular and Non-Valvular Atrial Fibrillation Population - Elzbieta Mlodawska; Anna Tomaszuk-Kazberuk; Paulina Lopatowska; Hanna Bachorzewska-Gajewska; Jolanta Malyszko; Slawomir Dobrzycki; Wlodzimierz Jerzy Musial (Karger Publishers, 2014)
Background/Aims: There are no data concerning renal function in population with valvular and non-valvular atrial fibrillation (AF). To assess renal function in patients with AF, the association between eGFR and AF perpetuation, in-hospital mortality. Methods: We studied 1523 patients with AF. Patients with chronic kidney disease (CKD) were compared to population with preserved renal function. Results: CKD was more frequently observed in patients with valvular AF(p=0.009). In non-valvular AF patients eGFR 2 had more often permanent AF(p2DS2VASc score was 4.1±1.5 and HAS-BLED score was 2.1±1.2 and it was higher as compared to population with preserved renal function (p75 years old(OR=3.70,p=0.01,95%CI1.33-10.28), with CKD (OR=2.61,p=0.03,95%CI1.09-6.23). The type of AF had no significant influence on in-hospital mortality(OR=0.71,p=0.45,95%CI0.30-1.70). Conclusions: CKD is more often observed in patients with valvular AF. In population with non-valvular AF decreased eGFR is associated with permanent type of AF and with higher CHA2DS2VASc and HAS-BLED score. Among valvular AF patients there are no differences in type of AF between patients with and without CKD. There is the correlation between CKD and AF perpetuation but only in non-valvular population.